Visual detection of serum asialohaptoglobin by plasmonic sandwich ELLSA – a new platform for cirrhosis diagnosis. Issue 1 (16th November 2015) - Bose, Partha Pratim; Mandal, Gautam; Kumar, Dharmendra; Duseja, Ajay; Chatterjee, Bishnu Pada
Abstract : A cheap, fast, point-of-care and high throughput visual assay platform for estimation of asialo-Haptoglobin to monitor liver cirrhosis. Abstract : The cirrhotic condition of the liver has long been acknowledged as the preface to liver cancer. The desialylation status of the serum acute phase protein, haptoglobin, has been introduced as a new diagnostic analyte for liver cirrhosis. The reliability of this new diagnostic molecule has been evaluated in 30 liver cirrhosis patients having a history of earlier viral hepatitis C (HCV-LC). A novel enzyme linked lectinosorbent assay has been developed coupled with the plasmon mechanism of gold nanoparticle aggregation as the colorimetric read out which can visually distinguish the cirrhotic liver patients from the normal healthy and hepatitis C controls. The assay can be useful for rapid point-of-care detection, and even an untrained person can execute it without a specialized instrument. This method employs Sambucus nigra agglutinin (SNA) to detect the extent of α-2, 6 sialylation of serum haptoglobin, the new diagnostic molecule for liver cirrhosis.